Implementasi Blended Learning Berbasis Moodle pada Mata Kuliah Perkembangan Peserta Didik - Siti Ermawati (IKIP PGRI Bojonegoro, 2022)
Abstract: This study aims to evaluate the application of Moodle-Based blended learning in Learning Development of Learners. This study focuses on two main studies, namely the application of blended learning and how it affects students. The research was carried out in one of the classes in the English Education Study Program of IKIP PGRI Bojonegoro for 14 meetings which were attended by 30 students. Data collection techniques used include; interviews, observations, and documentation. The results of this study indicate that (1) the application of Moodle-based blended learning in Learning Development of Learners runs smoothly, (2) most students (86.2%) agree that the use of Moodle-based blended learning helps them understand the learning material. Abstrak: Penelitian ini bertujuan untuk mengevaluasi penerapan blended learning Berbasis Moodle pada pembelajaran Perkembangan Peserta Didik. Studi ini berfokus pada dua kajian utama yaitu penerapan blended learning dan bagaimana dampaknya bagi mahasiswa. Penelitian dilaksanakan di salah satu kelas pada program studi pendidikan Bahasa Inggris IKIP PGRI Bojonegoro selama 14 Pertemuan yang diikuti oleh 30 mahasiswa. Teknik pengumpulan data yang digunakan antara lain; wawancara, observasi, dan dokumentasi. Hasil penelitian ini menujukkan bahwa (1) penerapan blended learning berbasis Moodle dalam pembelajaran Perkembangan Peserta Didik berjalan dengan lancar, (2) sebagian besar mahasiswa (86,2%) setuju bahwa penggunaan blended learning berbasis moodle membantu mereka memahami materi pembelajaran.